Role of image guided fine needle aspiration cytology in the diagnosis of intra-abdominal and intra-thoracic lesions - Choudhary, Mehnaz; Gupta, Rajat; Singh, Kuldeep (International Journal of Research in Medical Sciences, 2019)
Background: Intrathoracic and intra-abdominal tumors at inaccessible sites pose difficulty in diagnosis. Ultrasonography and computed tomography guided fine needle aspiration cytology has an important role in the diagnosis and distinguishing them as benign and malignant lesions. Image guided FNA has proved to be safe, quick, reliable and cost-effective method for obtaining tissue for cytopathological examination. The objective was to describe the pattern of intra-abdominal and intra thoracic masses on FNAC. Methods: This cross-sectional study was done in the postgraduate Department of pathology Government, Medical college Jammu i.e. 1st September 2017 to 30th September,2018 for a period of one year under image guided FNAC. Air dried and wet fixed smears were stained with may Grunwald Giemsa (MGG) and Papinacolau (PAP) stains respectively. Acid fast bacilli stain was done on additional smears in case of suspected tubercular lesions. Results: A total of 60 patients were subjected to ultrasonography and CT guided intra-abdominal and intra thoracic FNACs in a period of one year. FNAC was performed from various anatomical sites of which intra-abdominal lesions were 40 (liver:21 cases, gallbladder:8 cases, ovary: 3 cases, lymph nodes 3 cases, pancreas: 2 cases, omentum 2 cases, GIT 1 case). Intrathoracic lesions were twenty (20); out of which lung cases were eighteen (18) and two (2) were mediastinal aspirations. Conclusions: Percutaneous fine needle aspiration cytology under image guidance well described the pattern of deep-seated lesions.